Fluorescence properties of amido-substituted 2, 3-naphthalimides: Excited-state intramolecular proton transfer (ESIPT) fluorescence and responses to Ca2+ ions. Issue 43 (24th October 2019) - Wang, Lei; Fujii, Mayu; Namba, Misa; Yamaji, Minoru; Okamoto, Hideki
Graphical abstract: Highlights: 1-NHCOCF3 -2, 3-naphthalimide solely displayed normal FL. 1-NHMs-2, 3-naphthalimide displayed dual (normal and ESIPT) FL. The difference in the ESIPT fluorescence was explained by theoretical calculations. 1-NHCOCF3 -2, 3-naphthalimide showed no response to metal ions. 1-NHMs-2, 3-naphthalimide showed FL off-on response to Ca 2+ in the presence of DBU. Abstract: 2, 3-Naphthalimide derivatives incorporating trifluoroacetamido (3a ) and methansulfonamido (3b ) functionalities at the 1-position were prepared and their intramolecular excited state proton transfer (ESIPT) fluorescence and responses to metal ions were investigated. Compound3a displayed normal fluorescence in the amide form in toluene and MeCN and no response to metal cations in the corresponding amidate ion form. In contrast, compound3b gave off dual emission assignable to normal and ESIPT fluorescence. Additionally, the amidate form of compound3b displayed off-on fluorescence response to Ca 2+ .